PEMBUATAN ARCADE GAMES 2D ”BAGOUF” PADA PLATFORM WEB - Ivan, Derrick; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
“BagouF” is a game that consists of 6 minigames with Arcade and Single-player genre. This game can be played on the web platform on any gadget that has browsers. This game is developed with Unity2D and game assets created with Adobe Photoshop. Each minigame has their own unique gameplay. Players can share their highscore to twitter to keep their scores. The game is tested using blackbox testing method, alpha testing by advisors and beta testing with 33 respondents. The responses show that “BagouF” has interesting gameplay and easy to play.